Twelve months clinical outcome after bioresorbable vascular scaffold implantation in patients with stable angina and acute coronary syndrome. Data from the Polish National Registry - Rzeszutko, Łukasz; Siudak, Zbigniew; Tokarek, Tomasz; Plens, Krzysztof; Włodarczak, Adrian; Lekston, Andrzej; Ochała, Andrzej; Gil, Robert J.; Balak, Wojciech; Dudek, Dariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction : There are limited data describing bioresorbable vascular scaffold (BVS) implantation in complex lesions. Only short-term clinical outcomes are available for patients with acute coronary syndrome (ACS). Aim: To evaluate 12-month clinical outcome, safety and effectiveness of BVS implantation in complex lesions and in stable angina (SA) or ACS. Material and methods: Five hundred ninety-one patients with SA/ACS were enrolled between October 2012 and November 2013 in 30 invasive cardiology centres in Poland. At least one BVS implantation during percutaneous coronary intervention (PCI) was the only inclusion criteria. The clinical endpoint was the occurrence of a major adverse cardiovascular event (MACE) (all-cause death, myocardial infarction (MI), clinically driven target lesion revascularisation (TLR) with urgent PCI or target vessel revascularisation (TVR) with urgent coronary artery bypass grafting (CABG)) and device-oriented composite endpoint (DOCE) (cardiac death, urgent target vessel revascularisation with PCI/CABG, target vessel MI) during 12-month follow-up. Results: After 12 months TLR with urgent PCI was significantly more often reported in patients with diagnosed UA (4.59%; p < 0.02) in comparison with other PCI indications. No significant differences were found in terms of composite MACE endpoint, cumulative MACE (p = 0.09), stent thrombosis (p = 0.2) or restenosis (p = 0.2). There were no significant differences in cumulative MACE and composite MACE endpoint between patients with no/mild versus moderate/severe tortuosity and no/mild versus moderate/severe calcification of the target vessel. No significant difference was found between groups of patients with or without bifurcation of the target vessel. Device-oriented composite endpoint was significantly more often reported in the ACS group (3.2% vs. 0.47%; p < 0.03), most frequently in patients with diagnosed UA (5.5%). Conclusions : Bioresorbable vascular scaffold can be successfully and safely used for ACS treatment and in lesions of higher complexity.